Enhancing power generation and treatment of dairy waste water in microbial fuel cell using Cu-doped iron oxide nanoparticles decorated anode. (1st April 2019) - Sekar, Aiswarya Devi; Jayabalan, Tamilmani; Muthukumar, Harshiny; Chandrasekaran, Nivedhini Iswarya; Mohamed, Samsudeen Naina; Matheswaran, Manickam
Abstract: Performance of the bio-electrochemical treatment and power generation in microbial fuel cell (MFC) were examined by utilizing carbohydrates and proteins containing dairy effluent successfully. The efficiency of power production in MFC with nanoparticles modified anode was investigated. Copper doped iron oxide nanoparticles (Cu-doped FeO) were synthesized using phyto-compounds of A.blitum plant and characterized analytically. The nanoparticles coated and uncoated electrodes were characterized for wettability and electrochemical analysis. The wettability results of Cu-doped FeO coated anode showed good hydrophilic property. Cyclic voltammetry and electrochemical impedance spectroscopy results revealed increased potential and decreased resistance for coated anode. The performance of MFC exhibited, enhanced peak power density of 161.5 mW/m 2 for coated anode. The Chemical Oxygen Demand removal efficiency of nanoparticles coated and uncoated electrodes were 75 and 64.2% respectively. The results have suggested that the inexpensive Cu-doped FeO nanoparticles can be an effective material for treating dairy effluent and promoting the energy production in MFC. Graphical abstract: Synopsis: Schematic representation of Cu-doped iron oxide coated and uncoated anode electrode for comparison of MFC performance Highlights: Phyto-mediated synthesis of Cu-doped FeO nanoparticles with good physico-chemical traits. Cu-doped FeO nanoparticles coated anode holds good wettability and conductivity property. The efficiency of power generation and waste water treatment were enhanced with nanoparticles coated anode. The native bacteria present in dairy effluent showed resistant against nanoparticles.